Prescribing Pattern of Antimicrobials in the In Patients Department of Obstetrics and Gynaecology at A Tertiary Care Teaching Hospital at Nepal - Misra, A (International Journal of Pharmaceutical & Biological Archive, 2014)
Prescribing Pattern of Antimicrobials in the In Patients Department of Obstetrics and Gynaecology at A Tertiary Care Teaching Hospital at Nepal